Cartas entre Camilo José Cela y Martín de Riquer (1957-2000) - de Riquer, Isabel; Sotelo Vázquez, Adolfo (El Colegio de México, 2024)
The epistolary exchange between Camilo José Cela and Martín de Riquer, composing nearly fifty letters, began in October of 1957 and continued through to January of 2000. The main topics of these letters may be classified as follows: 1) the Cantar del Cid (1957-1960); 2) the Quijote (1965-1967, 1988); 3) the Diccionario secreto (1966, 1968); 4) and miscellaneous matters (RAE, congratulations on different occasions, the sending of books, etcetera).